Insan Kamil and Homo Deus: A Pinnacle of Human Existence in the Digital Era - Muhtar, Mohamad Khusnial; Bin Mohd Zailani, Ahmad Firdaus (University of Darussalam Gontor, Indonesia, 2024)
The human civilization in the current digital era is marked by advancements in artificial intelligence (AI) and reflective thought on human existence. This article aims to examine and to compare the pinnacle of human existence in the digital era from the perspectives of Muhammad Iqbal and digital anthropology. The issues discussed are the concepts of Insan Kamil in Iqbal and Homo Deus in digital anthropology, as well as the similarities and differences. The method used is library research with philosophical approach. The data obtained is analyzed qualitatively and comparatively. The results of this article include: the pinnacle of human existence, in Iqbal’s perspective, is understood as Insan Kamil, which is the best representation of divine vicegerent. Meanwhile, in digital anthropology, it can be understood as Homo Deus, which is human surpassing traditional biological limitations and approaching divine characteristics. Both perspectives share similarities in motivation to enhance well-being of humanity, recognizing evolution of human life, understanding the unlimited potential of each individual, and emphasizing the importance of obedience to laws and ethics. Whereas the differences emerge in applicability, religious aspects, achievement foundations, views on God, and the stance on digital technology use. Practically, this discussion raises indecision among practitioners due to the development and utilization of technology clearly separating these concepts. The recommendation for further research is alternative theories that bridge these intersecting ideas.